2013
DOI: 10.1080/21501203.2013.809026
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of arbuscular mycorrhizal fungi associated withFlemingia vestitaBenth. ex Baker

Abstract: Diversity of arbuscular mycorrhizal fungi (AMF) was investigated from natural (MF) and cultivated sites (TF) of Flemingia vestita Benth. ex Baker. Samplings were done at monthly intervals for one crop cycle. Root samples were evaluated for AMF colonization. Trap cultures were also established with four different host plants (Oryza sativa L., Paspalum notatum Flüggé, Trifolium repens L. and Zea mays L.) using rhizosphere soils from natural and cultivated sites of F. vestita as the source of AMF inoculum. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This study showed that F. geosporus produced spores under the aforementioned multiplication conditions, which reinforces the importance of TC for spore production and the identification of this species in Puna soils. Therefore, F. geosporus was a cryptic AM species concerning Puna field samples but a generalist species in TC as it has been reported after different TC approaches were used in several environments [ 4 , 14 , 15 , 16 ]. In this study, trap culture allowed the development and sporulation of AMF species which otherwise could not have been recovered from field soil.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…This study showed that F. geosporus produced spores under the aforementioned multiplication conditions, which reinforces the importance of TC for spore production and the identification of this species in Puna soils. Therefore, F. geosporus was a cryptic AM species concerning Puna field samples but a generalist species in TC as it has been reported after different TC approaches were used in several environments [ 4 , 14 , 15 , 16 ]. In this study, trap culture allowed the development and sporulation of AMF species which otherwise could not have been recovered from field soil.…”
Section: Resultsmentioning
confidence: 94%
“…However, this morphospecies was not found in field soils from AC ( Table 1 ) or It ( Table 2 ). Generally, F. geosporus is a quickly sporulating species but its spore abundance, both from field soil and TC, varies depending on land use [ 13 ] and edaphic properties [ 14 ]. In general, some authors suggest that AMF yield spores after 10 weeks of TC multiplication, which is in accordance with the previous two months’ report for F. geosporus TC [ 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations